ANALISIS MUTU ORGANOLEPTIK DAN UJI Salmonella sp. PADA IKAN CAKALANG ASAP DI PASAR REMU, KOTA SORONG - Sukmawati Sukmawati; Iksan Badaruddin; Azaria Lobat (Bioma, 2023)
Smoked skipjack is a type of product that is sold in many markets in Indonesia, including at Remu Market, Sorong City. However, the quality and safety of smoked skipjack tuna is a matter that needs to be considered by the public as consumers. The research method used was a descriptive study by observing the organoleptic quality of smoked skipjack tuna and detection on Salmonella sp..The results of this study showed that the organoleptic quality value of the appearance of the P sample of smoked skipjack tuna at the Remu market, Sorong city had the highest value of 8.87, then the highest odor test was 8.73, the taste value was 8.93, and the value of the texture was 8.40. However, the value of mushrooms and slime from the three samples showed the same value (9.0) which indicates that there was no fungus and slime in the smoked skipjack tuna observed. The results of the detection test Salmonella sp. showed that the P sample was safe from contamination by Salmonella sp. compared to sample R and sample Q.